Distinct Sleep Disturbance Profiles in Patients With Gastrointestinal Cancers Receiving Chemotherapy. Issue 2 (26th March 2022) - Lin, Yufen; Bailey, Donald E.; Docherty, Sharron L.; Porter, Laura S.; Cooper, Bruce A.; Paul, Steven M.; Hammer, Marilyn J.; Conley, Yvette P.; Levine, Jon D.; Miaskowski, Christine
Abstract : Background: Patients with gastrointestinal cancers experience moderate to high levels of sleep disturbance during chemotherapy that decreases their functional status and quality of life (QOL). Objective: The objectives of this study were to identify subgroups of patients with gastrointestinal cancers with distinct sleep disturbance profiles and evaluate for differences among these subgroups in demographic, clinical, and sleep characteristics, as well as co-occurring symptoms and QOL outcomes. Methods: Patients (n = 405) completed questionnaires 6 times over 2 cycles of chemotherapy. Latent profile analysis was used to identify subgroups of patients with distinct sleep disturbance profiles. Results: Three distinct sleep disturbance profiles (ie, low, high, very high) were identified. Compared with the low class, patients in the other 2 classes were significantly younger and less likely to be married and to exercise on a regular basis and received a higher number of previous treatments. Compared with the low class, patients in the other 2 classes reported higher levels of anxiety, depressive symptoms, morning and evening fatigue, and pain and lower levels of attentional function and QOL scores at enrollment. Conclusions: This study is the first to use latent profile analysis to identify subgroups of patients with gastrointestinal cancers with distinct sleep disturbance profiles. Findings provide new insights on the associations between sleep disturbance and multiple co-occurring symptoms in these patients. Implications for Practice: Clinicians can identify patients who are at the highest risk for sleep disturbance and recommend a variety of sleep hygiene interventions (eg, establishment of a bedtime routine), as well as initiate interventions for other co-occurring symptoms.